Pałac późnobizantyński i jego ceremoniał - Macrides, Ruth (Przegląd Nauk Historycznych, 2014)
The main aim of this article is to draw researchers’ and readers’ attention to neglected and underestimated Byzantine source known as Pseudo-Kodinos. The fourteenth-century text which is one of two surviving ceremonial books from the Byzantine empire, next to “Book of Ceremonies”, includes the combination of hierarchical lists of court officials with protocols of ceremonies; a detailed description of the clothing used at court; an account of the functions of the court title holders, a description of the ceremonies of the year which take place both inside the palace and outside and much more. Based on that, the author of the article is trying to bring developments in ceremonial which occurred since tenth century and discussed the space in which ceremonial was performed. Without any archeological research the author depicts the Blachernai palace, its setup and structure, its buildings and chambers, and compares it with those of Great Palace. In the article can be also found description of most important ceremonies which were held in the Blachernai Palace such as Christmas or Epiphany. Finally the author answers questions why Michael VIII Palaeologus, establishing new dynasty in Constantinople, chose as a place of his residence the Blachernai Palace.